2001
DOI: 10.1359/jbmr.2001.16.10.1739
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Selective Inhibition of Human Cathepsin K Leads to Inhibition of Bone Resorption In Vivo in a Nonhuman Primate

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(116 citation statements)
references
References 35 publications
(40 reference statements)
4
111
0
1
Order By: Relevance
“…When cathepsin K inhibitors were used in two different models of osteoporosis significant decreases in bone resorption were observed, however accompanied by secondary significant decreases in bone formation. 15,25 In our previous studies of the effect of a putative ClC-7 inhibitor in the aged rat OVX model, 28 evaluating bone resorption by CTX and formation by osteocalcin, as well as using dynamic histomorphometry indices of mineral apposition rate and mineralized surface index, we showed that by inhibition of acidification of the osteoclastic resorption lacunae, bone resorption was dose dependently inhibited without an effect on bone formation. This suggested that the signal for bone formation could be maintained despite the reduced resorption.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…When cathepsin K inhibitors were used in two different models of osteoporosis significant decreases in bone resorption were observed, however accompanied by secondary significant decreases in bone formation. 15,25 In our previous studies of the effect of a putative ClC-7 inhibitor in the aged rat OVX model, 28 evaluating bone resorption by CTX and formation by osteocalcin, as well as using dynamic histomorphometry indices of mineral apposition rate and mineralized surface index, we showed that by inhibition of acidification of the osteoclastic resorption lacunae, bone resorption was dose dependently inhibited without an effect on bone formation. This suggested that the signal for bone formation could be maintained despite the reduced resorption.…”
Section: Discussionmentioning
confidence: 86%
“…22 Bone formation remains to be carefully investigated in cathepsin K-deficient patients, however small molecule inhibitors of cathepsin K have been shown to cause both an inhibition of bone resorption and bone formation in various animal models. 15,25 The decrease in bone formation secondary to the decrease in bone resorption is possibly a result of the tight coupling of bone formation to bone resorption observed normally. From these combined observations, it could be speculated that acidification of the osteoclastic resorption compartment and dissolution of the inorganic phase of bone might be important for the proper coupling of bone resorption to bone formation.…”
mentioning
confidence: 99%
“…Representative images (c-F) of bone resorption pit formation in osteoassay plate evaluated in osteoclasts precursors cells from WT and NOD2 -/-mice cultivated with M-CSF + RANKL (control) and MDP 1 µg/mL. Bars = 100 µm (Mogi & Otogo, 2007;Garg et al, 2009) and matrix metalloproteinases (Leppilahti et al, 2014) were found in the gingival crevicular fluid of patients with periodontitis when compared to healthy patients, suggesting that the inhibition of cathepsin K may be a viable treatment for chronic diseases, such as periodontal disease (Stroup et al, 2001;Garg et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39][40][41] In addition, in nonhuman primate models, serum markers of bone resorption were also consistent with the observed phenotype. [42][43][44][45][46] Biomarkers of bone remodeling can also be used in in vitro models. 47 These cellular models can be reliably used for enhancing preclinical evaluation of pharmacological agents in metastatic bone disease.…”
Section: Preclinical Use Of Bone Remodeling Markersmentioning
confidence: 99%